Roles of local foundations in German community-based initiatives: Devolving criticism of philanthropy to the local? - Franz Koranyi; Nina Kolleck (Arizona State University, 2018)
This article explores perceptions of local philanthropic foundations situated in community-based initiative (CBI) policies that aim to achieve educational goals through the establishment of collaborative connections between schools and multiple local actors. Although roles of philanthropy in public education are controversial, scholars have yet to rigorously consider the specific local context of CBIs. We aim to help fill this research gap by investigating the main collective orientations that underlie actions of local foundations in German CBIs. Based on semi-structured interviews with chairpersons in a south German municipality, we examine patterns of experience and attitude through application of the documentary method. The reconstructed collective orientations allow for the identification of four primary roles of philanthropy in CBIs. Notably, the addition of an advocacy role relocates a phenomenon that was previously identified as a disruptive element at a (supra-)national level. These roles suggest potential for philanthropy to engage in local education policy-making. As such, they pose pressing questions that need to be addressed by public authorities and regulators.